A Basic Study for Modelling Logistics Network Design in Support of Decision Analysis - MATSUO, Toshihiko; FUJITANI, Hiromoto; MIKI, Tatehiko (Journal of Japan Logistics Society, 1996)
It is wellknown that tradeoff among several transportation services is governed by the transport capacity of each mode as well as its freight rates. The problem authors deal with is that of preparing a minimum cost transportation plan for rather sophisticated logistics network. In this paper, we present a solution method for this problem using a mixed integer programming medel with linear objective functions subject to all feasible traffic flows and all the combinations of constructing different candidate links. In order to illustrate the model, results are presented and discussed for case studies such as carrier selection in transportation services, and modalshift with multiple mode of transport.